Understanding the Growth Mechanism of GaN Epitaxial Layers on Mechanically Exfoliated Graphite - Tianbao Li (Nanoscale Research Letters, 2018)
Abstract The growth mechanism of GaN epitaxial layers on mechanically exfoliated graphite is explained in detail based on classic nucleation theory. The number of defects on the graphite surface can be increased via O-plasma treatment, leading to increased nucleation density on the graphite surface. The addition of elemental Al can effectively improve the nucleation rate, which can promote the formation of dense nucleation layers and the lateral growth of GaN epitaxial layers. The surface morphologies of the nucleation layers, annealed layers and epitaxial layers were characterized by field-emission scanning electron microscopy, where the evolution of the surface morphology coincided with a 3D-to-2D growth mechanism. High-resolution transmission electron microscopy was used to characterize the microstructure of GaN. Fast Fourier transform diffraction patterns showed that cubic phase (zinc-blend structure) GaN grains were obtained using conventional GaN nucleation layers, while the hexagonal phase (wurtzite structure) GaN films were formed using AlGaN nucleation layers. Our work opens new avenues for using highly oriented pyrolytic graphite as a substrate to fabricate transferable optoelectronic devices.